Off label and unlicensed drug use among French office based paediatricians. Issue 6 (1st December 2000) - Chalumeau, M; Tréluyer, J M; Salanave, B; Assathiany, R; Chéron, G; Crocheton, N; Rougeron, C; Mares, M; Bréart, G; Pons, G
Abstract : AIMS: To determine the extent of off label and unlicensed drug use in French office based paediatric practice. METHODS: A prospective one day survey of all written prescriptions, for patients under 15 years, among 95 office based paediatricians in the Paris, France metropolitan area. Main outcome measures were: comparison of the use of each drug with its product licence for age, indication, dose, and route of administration. RESULTS: A total of 2522 prescriptions were administered to 989 patients; 844 (33%) were used either in an unlicensed (4%) or an off label (29%) manner. A total of 550 (56%) paediatric patients received one or more off label prescriptions. CONCLUSIONS: Off label prescriptions (that is, outside the terms of the Summary of Product Characteristics) are widespread in office based paediatric practice, while unlicensed drug use is rare in our study. New regulations in the licensing process in Europe are needed to allow children to receive drugs that have been fully evaluated in their specific age group.